Pengaruh Iklan, Sistem COD, dan Promo Gratis Ongkir Terhadap Keputusan Pembelian Pada TikTokShop (Studi Kasus Pada Mahasiswa UIN Sumatera Utara) - Irma Rahmayani Marpaung; Fauzi Arif Lubis (FEB Universitas Sam Ratulangi Manado, 2022)
ABSTRACTOf the many e-commerce sites that have sprung up in Indonesia, the TikTok application takes this business opportunity by creating a TikTok Shop which is a digital marketing medium that is no less widely used by business people. The purpose of this study is to find out how much influence advertising, the COD system and free shipping promo have on purchasing decisions at the TikTok Shop among UIN North Sumatra students. The research method used is quantitative. The data used in this study are primary data obtained from questionnaires. The sample of this research was students of the State Islamic University of North Sumatra, totaling 100 respondents. The analysis technique uses multiple linear analysis. The variables of this study consist of independent variables, namely advertising, the COD system, and free shipping promos and the dependent variable, namely purchasing decisions at the TikTok Shop. The results of the study show that advertising, COD systems and free shipping promos have a positive and significant effect on purchasing decisions simultaneously. Partial testing results: advertising has a significant effect on purchasing decisions indicated by tcount 1990 and ttable 1985. The COD system has a significant effect on purchasing decisions shown by the tcount of 2.306 and ttable of 1.985. The free shipping promo has a significant effect on purchasing decisions as indicated by the tcount of 3,452 and ttable of 1,985. Keywords: Advertising, COD System, Free Shipping Promo, Purchase Decision